In Vitro Effects of the Endocrine Disruptor p,p’-DDT on Human Follitropin Receptor - Munier, Mathilde (Environ Health Perspect, 2016)
BACKGROUND: 1-chloro-4-[2,2,2-trichloro-1-(4-chlorophenyl)ethyl]benzene (p,p′-DDT) is a persistent environmental endocrine disruptor (ED). Several studies have shown an association between p,p′-DDT exposure and reproductive abnormalities. OBJECTIVES: To investigate the putative effects of p,p′-DDT on the human follitropin receptor (FSHR) function. METHODS: and Results: We used Chinese hamster ovary (CHO) cells stably expressing human FSHR to investigate the impact of p,p′-DDT on FSHR activity and its interaction with the receptor. At a concentration of 5 μM p,p′-DDT increased the maximum response of the FSHR to follitropin by 32 ± 7.45%. However, 5 μM p,p′-DDT decreased the basal activity and did not influence the maximal response of the closely related LH/hCG receptor to human chorionic gonadotropin (hCG). The potentiating effect of p,p′-DDT was specific for the FSHR. Moreover, in cells that did not express FSHR, p,p′-DDT had no effect on cAMP response. Thus, the potentiating effect of p,p′-DDT was dependent on the FSHR. In addition, p,p′-DDT increased the sensitivity of FSHR to hCG and to a low molecular weight agonist of the FSHR, 3-((5methyl)-2-(4-benzyloxy-phenyl)-5-{[2-[3-ethoxy-4-methoxy-phenyl)-ethylcarbamoyl]-methyl}-4-oxo-thiazolidin-3-yl)-benzamide (16a). Basal activity in response to p,p′-DDT and potentiation of the FSHR response to FSH by p,p′-DDT varied among FSHR mutants with altered transmembrane domains (TMDs), consistent with an effect of p,p′-DDT via TMD binding. This finding was corroborated by the results of simultaneously docking p,p′-DDT and 16a into the FSHR transmembrane bundle. CONCLUSION: p,p′-DDT acted as a positive allosteric modulator of the FSHR in our experimental model. These findings suggest that G protein–coupled receptors are additional targets of endocrine disruptors. CITATION: Munier M, Grouleff J, Gourdin L, Fauchard M, Chantreau V, Henrion D, Coutant R, Schiøtt B, Chabbert M, Rodien P. 2016. In vitro effects of the endocrine disruptor p,p′-DDT on human follitropin receptor. Environ Health Perspect 124:991–999; http://dx.doi.org/10.1289/ehp.1510006